Tomorrow's a mystery: constructions of the future and 'un/becoming' amongst 'early' and 'late' career academics. Issue 4 (2nd October 2018) - Read, Barbara; Leathwood, Carole
Abstract: Constructing a secure sense of a professional future has become increasingly difficult for early career researchers, whilst concerns about present and future job in/security have also been expressed in relation to already-established academics. In this paper, we draw on qualitative data from a U.K. study to explore everyday conceptualisations of the future for both 'early career' and 'late career' academics, in the context of increased fears and actualities of occupational precarity. We utilise theories of the social construction of time, as well as a conception of precarity and 'precarization' utilised by Butler (2009a, 2009b) and Lorey (2015), relating to 'politically induced' forms of insecurity that are a direct product of neoliberalism. The research reveals a variety of forms and levels of concern and anxiety by both groups for their own futures, and for the future of the academy as a whole.